The Influence of Pre-Market and After-Market Trading in Financial Market: An Experimental Analysis - WU, Yueao (2013)
Abstract: The pre- market and after-market trading is no longer a new thing in the stock and currency trading markets, Due to the development of electronic communication network, the investors and traders can operate the trading transactions outside stock exchanges and have more flexibility of trading time.